SYNTACTIC PARALLELISM IN ENGLISH POETRY: A COGNITIVE STYLISTIC PERSPECTIVE - Kuchimova Nargiza Ulugbekovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This paper explores the role of syntactic parallelism in English poetry through the lens of cognitive stylistics. Drawing on diverse literary analyses and theoretical models, it demonstrates how structural repetition enhances poetic meaning, reader engagement, and emotional resonance. The study underscores the cognitive function of parallel syntax as a tool for conceptual framing, aesthetic depth, and interpretive accessibility.